2017
DOI: 10.17582/journal.jap/2017/4.2.33.40
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Intestinal Parasites among Elementary School children in Sohag, Egypt

Abstract: Intestinal parasitic infections (IPIs) are of the maximum generic of human infections international, causing extensive morbidity and mortality particularly in children. Our aim was to estimate the situation of IPIs in stool and fingernails samples among elementary schoolchildren in Sohag, Egypt. In this cross-sectional research stool specimens from 200 schoolchildren were inspected macroscopically and microscopically by formol-ether sedimentation, after that staining with Kinyoun's modified acid-fast stain. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 0 publications
11
18
1
Order By: Relevance
“…Abroad, Mekonnen and Ekubagewargies (2019) reported that the prevalence of intestinal parasites was (18.7%) in Northwest Ethiopia in younger children, Ismail (2018) in Saudi Arabia, Taif reported a prevalence of (12%) in school children. But, El-Nadi et al (2017) found a higher (63.5%) prevalence among school children. The present prevalence was lower than studies done in different developing and undeveloped countries (Ulukanligil and Seyrek, 2003;Jiraa-monninit et al, 2006;Awolaju and Morenikeji, 2009;Aly and Mostafa, 2010;Ayalew et al, 2011;Gelaw et al, 2013;Sah et al, 2013).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Abroad, Mekonnen and Ekubagewargies (2019) reported that the prevalence of intestinal parasites was (18.7%) in Northwest Ethiopia in younger children, Ismail (2018) in Saudi Arabia, Taif reported a prevalence of (12%) in school children. But, El-Nadi et al (2017) found a higher (63.5%) prevalence among school children. The present prevalence was lower than studies done in different developing and undeveloped countries (Ulukanligil and Seyrek, 2003;Jiraa-monninit et al, 2006;Awolaju and Morenikeji, 2009;Aly and Mostafa, 2010;Ayalew et al, 2011;Gelaw et al, 2013;Sah et al, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…The gastro-intestinal parasites included: A. lumbricoides (11.4%), G. lamblia (10%), E. coli (9.7%), A. duodenale (8.7%), E. histolytica (8.1%), C. -Nadi et al, 2017). Also, data were in line with studies conducted in Nigeria and Ethiopia (Adeyeba and Akinlabi, 2002;Ukpai and Ugwu, 2003;Banke et al, 2006;Awolaju and Morenikeji, 2009;Ayalew et al, 2011;Gelaw et al, 2013;Mengistu et al, 2014;Teklemariam et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infective stages of many IPs can be collected from raw fruits/vegetables which results in ingestion of parasites while eating. 25 Therefore, it is justifiable that psychiatric patients with a habit of consuming unwashed raw fruits/vegetables are at higher risk of parasitic infections. Psychiatric patients with bipolar disorder are known for keeping good personal hygiene and giving value for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted in Sohag Governorate revealed that only 4% of the examined school children were infected with helminth parasites with predominance of H. nana. This could be a result of increase in the general awareness about personal hygiene and ways of parasites transmission or could be a result of anthelminth campaign carried out in Egypt [52] .…”
Section: Discussionmentioning
confidence: 99%